Thyme (Thymus vulgaris) as an antimicrobial agent in the production of fresh cheese - Mejía López, Ana (2017)
The effect of the use of the thyme Thymus vulgaris leaves in the development of. Staphylococcus aureus, a microorganism that is associated with outbreaks of food poisoning and which is commonly present in fresh cheese of the artisanal type, for this purpose, cheese was prepared by inoculating strains of S. aureus ATCC 25923 previously suspended with a turbidity equivalent to the scale of 0.5 McFarland, and was evaluated through a completely randomized design with 3 replicates, where the factors under study were 2 types of processes (1) in sheets incorporated in cheese, (2) in infusion in salty water, and 4 Concentrations (0, 1, 075 and 0.5%). Colony-forming units were determined following the official APHA methodology on days 1, 8, 15, and 30 after their production. As a result, a signiﬁcant reduction of the microbial load in the experimental plates (1 and 075% with thyme) was obtained in comparison to the control plates (0%) in process 1, whereas there was reduction for all the concentrations tested when added the infused thyme during the salting of the cheese. Concluding that at greater concentration of thyme greater inhibitory effect on S. aureus and could be used in the preservation of food as the main natural antimicrobial compounds in order to ensure the production of microbiologically stable food.